ON THE CHARACTERIZATION AND SOLVABILITY OF INFINITE ORDER LINEAR DISCRETE DIFFERENCE EQUATIONS - A.V. BRATISHCHEV; L.I. KALINICHENKO (Advanced Engineering Research, 2007)
Authors give the solution of linear discrete difference equation of infinite order, in the sequences space., They propose description of correspondence difference operators in the classes of infinite matrix operators.